(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic cracking of the lips is currently considered a chronic disease of the red border, mucous membrane of the lips, and corners of the mouth, accompanied by a linear disruption of lip tissue integrity. To date, numerous methods for diagnosing and treating chronic cleft lip have been proposed, including both general and local treatment regimens. However, the number of patients with this pathology tends to constantly increase, therefore, the search for new drugs and methods for its treatment is important and justified. The article presents a clinical case of local treatment of chronic lower lip fracture, including local anesthetic blockade and the application of a collagen-containing drug, which showed good clinical results.